Pulmonary artery in situ thrombosis due to patent ductus arteriosus: a case report - Wang, Yin; Rong, Chunyan; Lu, Ming; Zhang, Weihua (Frontiers in Cardiovascular Medicine, 2024)
Background Pulmonary Artery in situ Thrombosis (PAIST) refers to a thrombus forming within the pulmonary arterial system, distinct from an embolus originating from elsewhere in the body (e.g., the deep veins of the lower extremities) and traveling to the lungs where it lodges and forms. Case presentation We present a case of PAIST caused by the arterial ductus arteriosus. The patient primarily presented with dyspnea, and the chest pain dichotomy Computed Tomography Angiography(CTA) suggested that a nodular low-density filling defect was seen in the lumen of the left pulmonary artery trunk. Initially, pulmonary embolism (PE) was suspected. However, upon reevaluation of the imaging, it became apparent that the patient's pulmonary artery obstruction was closely associated with the ductus arteriosus. After admission, the patient was treated with sodium ampicillin (2.0 g Q12H) for infection, heparin sodium (5,000 IU Q12H) for anticoagulation, and metoprolol succinate extended-release tablets (23.75 mg QD) to correct cardiac remodeling, among other treatments. Subsequently, the patient underwent a cardiac surgery involving the ligation of the arterial duct, resection of pulmonary artery lesions, and open-heart surgery with extracorporeal circulation support. Postoperative examination of the pulmonary artery mass indicated coagulation tissue. The final diagnosis was “PAIST”. Conclusion Both PAIST and PE manifest as low-density filling defects in the pulmonary arteries. However, due to the relative unfamiliarity with PAIST, such findings are often initially attributed to PE.